Modeling of system factors of financial security of agricultural enterprises of Ukraine - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Prystеmskyi, O.S.; Hryvkivska, O. V.; Sakun, Alina Zh.; Kyrylov, Yurii Y. (My University, 2021)
The article considers the process of modeling of systemic factors of financial security of agricultural enterprises of Ukraine. The methodology of complex, systematic assessment of fiscal security and mathematical tools in the deterministic space of the financial system of enterprises are substantiated. A systematic approach is used, which determines the quantitative and qualitative parameters of external and internal threats, identifies the threshold interval of stable financial condition and stable development of agricultural enterprises. Systemic factors of stimulating and disincentive character for an estimation of financial safety of the agricultural enterprises are developed. A set of indicators for the analysis of the state of the functional components of financial security, provided by the process of neutralization of real and potential threats to the stable potential of financial security of enterprises is determined. The expediency of normalization of indicators is substantiated, their threshold values, weights and capital structure are taken into account when calculating the integrated level of financial security. It is proved that the introduction of systemic factors in the general level of financial security allows increasing the level of financial stability and reliability of agricultural enterprises.
Keywords: financial security; potential of financial security; efficiency; threats; agricultural enterprises; financial condition; financial balance